Proceedings of the 25th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (IEEE Cat. No.0
DOI: 10.1109/iembs.2003.1280126
|View full text |Cite
|
Sign up to set email alerts
|

Subspace and envelope subtraction algorithms for noise reduction in cochlear implants

Abstract: The performance of two noise reduction algorithms is evaluated using 14 subjects fitted with the Clarion S-Series and Clarion I1 implant devices. The first algorithm, based on signal subspace principles, is used for preprocessing sentences embedded in +5 dB noise. The second algorithm is based on the subtraction of the noisy speech envelopes from an estimate of the noise envelopes. The noise envelopes are estimated continuously using a variation of the minimum statistics algorithm. Results showed that the subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Ideally, noise reduction algorithms should be easy to implement and be integrated into the existing coding strategies. Only a few algorithms [100,101] were proposed along this direction.…”
Section: Single-microphone Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, noise reduction algorithms should be easy to implement and be integrated into the existing coding strategies. Only a few algorithms [100,101] were proposed along this direction.…”
Section: Single-microphone Methodsmentioning
confidence: 99%
“…Toledo et al [100] proposed a simple envelope subtraction algorithm based on the principle that the clean (noise-free) envelope can be estimated by simply subtracting the noisy envelope from the noise envelope. This approach requires estimate of the noise envelope, which can be obtained using a noise estimation algorithm -an algorithm that continuously tracks the noise envelope even during speech activity.…”
Section: Single-microphone Methodsmentioning
confidence: 99%
“…To compensate for the impaired ability to understand speech in noise, many noise suppression algorithms have been proposed for cochlear implants ͑Hamacher et al, 1997; Toledo et al, 2003;Weiss, 1993;Wouters and Vanden Berghe, 2001;van Hoesel and Clark, 1995͒. These algorithms use either single microphone or dual microphones and can be adaptive or nonadaptive in nature.…”
Section: Introductionmentioning
confidence: 97%
“…For CI recipients, several studies reported that single-microphone noise reduction techniques improve speech intelligibility in background noise with limited temporal fluctuations (Hochberg et al 1992;Toledo et al 2003;Yang & Fu 2005;Kasturi & Loizou 2007;Buechner et al 2010;Dawson et al 2011;Mauger et al 2012). The reported improvements are modest to small.…”
Section: Introductionmentioning
confidence: 99%